Finding the best estimation of generalized for failure rates by using Simulation - البدري فاتن فاروق; فرج علا علي (Journal of Economics and Administrative Sciences, 2012)
The statistical distributions study aimed to obtain on best descriptions of variable sets phenomena, which each of them got one behavior of that distributions . The estimation operations study for that distributions considered of important things which could n’t canceled in variable behavior study, as result this research came as trial for reaching to best method for information distribution estimation which is generalized linear failure rate distribution, throughout studying the theoretical sides by depending on statistical posteriori methods like greatest ability, minimum squares method and Mixing method (suggested method). The research has contained such a comparing between sixth estimations methods for generalized linear information of failure rates distribution (GLFRD), by depending on two important statistical measurements which are: error squares medial (MSE), absolute relative error medial (MAPE), for obtaining on the best estimation method .